2022
DOI: 10.3390/cancers14184495
|View full text |Cite
|
Sign up to set email alerts
|

CTRP1 Knockout Attenuates Tumor Progression in A549 and HCT116 Cancer Cells

Abstract: C1q and TNF-related 1 (C1QTNF1/CTRP1) is an adiponectin-associated protein belonging to the C1q/TNF-related protein family. Recent studies have shown that the C1q and TNF-related protein (CTRP) family is involved in cancer progression; however, the specific role of CTRP1 in tumor progression has not yet been elucidated. To examine the role of CTRP1 in tumor progression, we generated CTRP1 knockout A549 and HCT116 cell lines, which reduced the expression levels of nuclear factor (NF)-κB-dependent and metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cell migration is a vital part of ocular surface wound healing and essential to restore integrity of the physiological barrier of the eye [ 1 , 60 ]. Several studies have described enhanced cell proliferation and migration as well as tumor invasion through CTRP1, CTRP6, or CTRP8 [ 5 , 7 , 19 , 20 , 21 , 30 , 31 , 63 ]. For example, CTRP8 promotes cell migration in human glioblastoma cells by activation of the RXFP1 involving the N-terminal “YAAFSVG” peptide motif present in the C1q globular domain of CTRP8 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration is a vital part of ocular surface wound healing and essential to restore integrity of the physiological barrier of the eye [ 1 , 60 ]. Several studies have described enhanced cell proliferation and migration as well as tumor invasion through CTRP1, CTRP6, or CTRP8 [ 5 , 7 , 19 , 20 , 21 , 30 , 31 , 63 ]. For example, CTRP8 promotes cell migration in human glioblastoma cells by activation of the RXFP1 involving the N-terminal “YAAFSVG” peptide motif present in the C1q globular domain of CTRP8 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that C1QTNF1 expression is increased in obese mice, and overexpression of C1QTNF1 can inhibit the transcription and protein expression of the tumor suppressor gene P53, leading to tumor progression ( Park et al, 2021 ). Knockdown of C1QTNF1 in A549 and HCT116 resulted in tumor cell proliferation, invasion, and growth ( Park et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the diverse functions of C1QTNF1 in immunity, metabolism and endocrine. It has been demonstrated that knockout of C1QTNF1 inhibits cell proliferation and invasion as well as tumor growth by generating C1QTNF1 knockout human lung cancer and human colon cancer cell lines ( Park et al, 2022 ). Meanwhile, C1QTNF1 has also been found to be widely involved in the regulation of a variety of inflammatory responses, such as the association of C1QTNF1 levels with coronary artery disease ( Shen et al, 2019 ); C1QTNF1 suppressed porcine circovirus type 2 ( PCV2 ) replication ( Cao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%